The Interplay Between Creative Production and Emotional Experience: The Influence of Emotional States and Creativity Motivation Among University Students - Gorica Popovska Nalevska (Scientia Publica Media, 2026)
The general aim of the research is to investigate the dynamic relationship between creative production and emotional experience, with a particular focus on how engagement in creative activities shapes emotional states and how varying emotional states, in turn, influence the quality, originality, and overall character of creative outcomes among university students. Creativity is considered a complex process influenced by both positive and negative moods, which can stimulate different aspects of flexible thinking, persistence, and originality. For students, emotions are particularly relevant as they navigate academic challenges and personal development, making creative expression not only a tool for learning but also an outlet for self-regulation and growth. The research was conducted on a sample of 150 psychology students from universities in the Republic of North Macedonia. A descriptive-analytical method was applied, using a self-report questionnaire that measured students’ emotional experiences during creative work as well as their perceptions of creativity. Additionally, a culturally adapted scale for measuring creativity motivation was included to ensure relevance to the local academic context. Results show that the relationship between emotional states and creativity is strong, supporting the idea that well-being directly influences creative potential. This indicates that creativity is not only an outcome influenced by emotions but also a strategy for emotional regulation and psychological well-being. Findings suggest that the student sample demonstrates a well-balanced creative motivation profile. The results also carry important implications for the educational context. Fostering a supportive and emotionally positive learning environment may directly contribute to students’ creative potential.